Estudio de la Interconectividad y la Seguridad de los Datos en los InfoCentros de la Ciudad de Babahoyo - Chonillo Montece, Hugo Alexander (2017)
The community InfoCentros are public places where various users come to learn about the advances of technology, it is also useful to perform tasks or jobs. Keeping this space open to the public becomes vulnerable to attacks from the servers. The servers are in charge of hired facilitators, besides being in charge of the InfoCentros they teach computer classes, among other courses. In the InfoCentros you get information of all the data of the citizens that come to the place to be trained, because the data of the inscriptions in the courses are stored in the server and this is vulnerable, because they handle electronic mail to communicate frequently , this would be the breach to extract any type of information stored on the server. The way to reduce risks involving user data is the implementation of rules and measures for the protection of the information of the InfoCentros. The ISO27001: 2013, "Information Security Management System, results to improve properly and to determine several threats, setting strategies and controls necessary to safeguard information." (ISOTools Excellence, 2015) The e-mails that have the InfoCentros, do not maintain any type of security other than the one of the own mail, the communication that the InfoCentros makes are through public emails, does not have institutional mails, which makes it possible to hack the account of the mail and have access to the data with ease.